Marketization of the Chinese labor market and the role of unions - Max J. Zenglein (International Labour Organization (ILO), 2008)
This paper will provide insight to recent developments in Chinese labor markets and the current role of trade unions. The Chinese labor market has changed dramatically within the past few decades, moving from a centrally planned economy to a more market oriented one. The marketization of the Chinese labor market has contributed in creating an employer dominated labor market and potential social conflict among the labor force. Recent government efforts have attempted to improve industrial relations and in these efforts the role of trade unions has also been evolving. However, Chinese trade unions are not independent and face considerable constraints in achieving their objectives.
Keywords: 330